A glance from Rorschach towards the intellectually talented children at risk - Blumen, Sheyla (2006)
Personality characteristics of the intellectually gifted living under poverty conditions are des-cribed, following the Rorschach Psychodiagnostic test. Participants were 55 boys and girls (27 intellectual gifted, 28 non-gifted), age range 9-12, previously selected with the Multi-factorial model of giftedness for a former study. Results revealed that the intellectually gifted children ex- hibit the following personality characteristics: (a) tendency to approach situations from personal reflections; (b) sophisticated emotional resources; (c) high levels of initiative and creativity; (d) tendency to perfectionism; (e) need to control situations; (f) unconventionality; (h) high levels of sensibility; (i) oppositeness, as well as (j) insight resources. They also exhibit characteristics expected in poverty contexts such as cautiousness and low level of self-confidence, high levels of stress and alert towards the environment, as well as tendency to depression. Recommendations for intervention purposes are given, as well as the need to develop research lines from a multidis-ciplinary approach.